2020
DOI: 10.1016/j.abd.2020.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Atypical manifestations of recent syphilis: study of 19 cases

Abstract: Background Syphilis is one of the most common diseases that start with genital ulcers. Aside from the initial, classic ulcerative lesion of syphilis, called hard chancre, atypical presentations are common, with erosions, erythema, edema, balanitis, and other dermatological manifestations. Associated with initial genital lesions, the presence of inguinal adenopathies is frequent, and the presence of hardened and painless lymphangitis on the dorsum of the penis is rare. Objectives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In 1978, Chapel found that less than half (42.7%) of patients with PS he diagnosed presented typical single, indurated chancres with regional lymphadenopathy, suggesting that the “classic” chancre may be the “atypical” lesions [ 15 ]. However, beyond many case report [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ] and narrative review [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ] syphilis manifestations, very few studies and/or case series including more than five cases with atypical syphilis manifestations have been published in the English literature during the past 20 years [ 32 , 33 , 34 , 35 , 36 , 37 , 38 ] ( Table 4 ). Cases of atypical primary syphilis misdiagnosed as pharyngeal lymphoma, tongue cancer, and other types of oral squamous cell carcinomas have been described [ 39 , 40 , 41 ]; however, the secondary stage of the disease, given the possible involvement of the whole skin area and of other organs, is the one that is most prone to misdiagnosis like palmoplantar psoriasis, psoriasis vulgaris, erythema multiforme, cutaneous lymphoma, and granulomatous diseases of the skin (annular granuloma, sarcoidosis).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1978, Chapel found that less than half (42.7%) of patients with PS he diagnosed presented typical single, indurated chancres with regional lymphadenopathy, suggesting that the “classic” chancre may be the “atypical” lesions [ 15 ]. However, beyond many case report [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ] and narrative review [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ] syphilis manifestations, very few studies and/or case series including more than five cases with atypical syphilis manifestations have been published in the English literature during the past 20 years [ 32 , 33 , 34 , 35 , 36 , 37 , 38 ] ( Table 4 ). Cases of atypical primary syphilis misdiagnosed as pharyngeal lymphoma, tongue cancer, and other types of oral squamous cell carcinomas have been described [ 39 , 40 , 41 ]; however, the secondary stage of the disease, given the possible involvement of the whole skin area and of other organs, is the one that is most prone to misdiagnosis like palmoplantar psoriasis, psoriasis vulgaris, erythema multiforme, cutaneous lymphoma, and granulomatous diseases of the skin (annular granuloma, sarcoidosis).…”
Section: Discussionmentioning
confidence: 99%
“…The phagedenic chancres have been historically associated with pyogenic superinfections (Streptococcus agalactiae in one of our cases), which cause an extensive loss of substance; in other instances, immunosuppression due to HIV infection and/or alcoholism may cause the loss of local cellular immunity, favoring the massive local diffusion of the T. pallidum infection [ 29 , 38 ]. None of our patients with phagedenic chancres were HIV-seropositive, but one was a heavy drinker and the other used soft drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical presentations of syphilis, in all phases, are varied, and most scholars in this area consider it "the great imitator" [29] . This is because the manifestations histologically and clinically mimic a wide variety of infectious, neoplastic and immune diseases.…”
Section: Clinical Manifestationsmentioning
confidence: 99%